2020
DOI: 10.1186/s12909-020-02310-2
|View full text |Cite
|
Sign up to set email alerts
|

Student satisfaction with videoconferencing teaching quality during the COVID-19 pandemic

Abstract: Background The coronavirus disease 2019 pandemic prompted the pediatric department at King Abdulaziz University to continue students’ educational activities by offering courses online that utilized web video conferencing (WVC). Given the uncertainties of WVC educational quality and the challenge of shifting to an online environment, this study aimed to evaluate student satisfaction with the teaching quality of case-based discussion (CBD) sessions conducted through WVC. Methods One hundred sixty-two undergrad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
110
4
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 29 publications
18
110
4
7
Order By: Relevance
“…Therefore, instructors play an important role in enhancing the concentration, motivation, and level of understanding of learners, and facilitating quality online learning, in particular when the class is conducted through video conferencing tools. This was in line with the study conducted by Fatani (2020) and Alqurashi (2018) which showed the importance of instructor presence and instructor-learner interaction based on the community of inquiry (COI) framework [20,43].…”
Section: Important Predictorssupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, instructors play an important role in enhancing the concentration, motivation, and level of understanding of learners, and facilitating quality online learning, in particular when the class is conducted through video conferencing tools. This was in line with the study conducted by Fatani (2020) and Alqurashi (2018) which showed the importance of instructor presence and instructor-learner interaction based on the community of inquiry (COI) framework [20,43].…”
Section: Important Predictorssupporting
confidence: 90%
“…Therefore, the technical barrier or underdeveloped infrastructure was not likely the key factor contributing to the low satisfaction score on ERL. This supported the finding observed from another recent study conducted by Fatani (2020) that technical issues (audio/visual) were not the significant determinants of student satisfaction using ERL during the pandemic [20]. Both studies somewhat echoed and associated with the idea raised by Alqurashi et al (2018) that computer and internet self-efficacies were not important in determining student satisfaction in online learning [43].…”
Section: Important Predictorssupporting
confidence: 85%
“…Universities stopped face-to-face education and have been advised to rapidly offer online learning tools [ 7 ]. University staff and educators had to meet new online education challenges: demonstrating pedagogical skills in an online classroom, addressing their managerial role, establishing relationships with students, and providing technical support [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 disease has popularized video conferencing tools for synchronous teaching sessions, meeting, or tutoring. Students feel highly satisfied with the videoconferences teaching quality [47]. However, different difficulties with this system might be underlined, such as class rhythm, problems for interacting with the teachers and peers, attention and procrastination issues, etc.…”
Section: Infrastructure Layermentioning
confidence: 99%